Customer economics of residential PV–battery systems in Thailand - Chaianong, Aksornchan; Bangviwat, Athikom; Menke, Christoph; Breitschopf, Barbara; Eichhammer, Wolfgang (Renewable Energy, 2020)
The currently high upfront costs of batteries and the low retail electricity prices of households make investments in PV–battery systems not yet economically feasible. However, the experiences/learning curves of renewable generation technologies lead to the assumption that battery prices will rapidly decline with increasing diffusion. Furthermore, projected retail electricity rates are expected to increase with rising electricity demand. This study investigates the returns to residential customers using PV–battery systems under decreasing battery prices in Thailand. The impacts of four additional parameters have been included. The analysis is based mainly on net present values (NPV) and levelized costs of electricity (LCOE). The results show that battery size and its cost, and retail rate design have significant impacts on the returns, whereas buyback incentives for excess electricity have the lowest impact. In addition, to increase the power system flexibility by using PV–battery systems, the Thai government should provide the appropriate financial support, by which the savings incurred by the grid extension investments compensate for the costs.
Created from Fastlane, Scopus look-up
Keywords: Battery; Customer economics; PV; Residential; Rooftop; Thailand